Low-cost, disposable microfluidics device for blood plasma extraction using continuously alternating paramagnetic and diamagnetic capture modes - Kim, Pilkee (2016)
Blood plasma contains biomarkers and substances that indicate the physiological state of an organism, and it can be used to diagnose various diseases or body condition. To improve the accuracy of diagnostic test, it is required to obtain the high purity of blood plasma. This paper presents a low-cost, disposable microfluidics device for blood plasma extraction using magnetophoretic behaviors of blood cells. This device uses alternating magnetophoretic capture modes to trap and separate paramagnetic and diamagnetic cells away from blood plasma. The device system is composed of two parts, a disposable microfluidics chip and a non-disposable (reusable) magnetic field source. Such modularized device helps the structure of the disposable part dramatically simplified, which is beneficial for low-cost mass production. A series of numerical simulation and parametric study have been performed to describe the mechanism of blood cell separation in the microchannel, and the results are discussed. Furthermore, experimental feasibility test has been carried out in order to demonstrate the blood plasma extraction process of the proposed device. In this experiment, pure blood plasma has been successfully extracted with yield of 21.933% from 75 μl 1:10 dilution of deoxygenated blood.